A dual-emission ratiometric fluorescent sensor based on copper nanoclusters encapsulated in zeolitic imidazolate framework-90 for rapid detection and imaging of adenosine triphosphate. Issue 6 (24th January 2023) - Xin, Yue; Zhang, Dun; Zeng, Yan; Wang, Yingwen; Qi, Peng
Abstract : A dual-emission ratiometric fluorescent sensor Cu NCs–Al@ZIF-90 was synthesized for ATP detection. The fluorescence emission of Cu NCs and 2-ICA induced by ATP addition was changed reversely and independently. Abstract : Adenosine triphosphate (ATP) is the primary energy carrier for intracellular metabolic processes. Accurate and rapid detection of ATP has important implications for clinical diagnosis. In this work, we reported a dual-emission ratiometric fluorescent probe Cu NCs–Al@ZIF-90 formed by encapsulating copper nanoclusters (Cu NCs) into zeolitic imidazolate framework-90 (ZIF-90) using a simple one-pot method. Cu NCs exhibited a remarkable fluorescence enhancement in the presence of aluminum ions due to the aggregation-induced emission (AIE) properties. When ATP existed, the Zn 2+ nodes in the MOF material acted as selective sites for ATP recognition, resulting in the cleavage of Cu NCs–Al@ZIF-90. As a consequence, two reverse fluorescence changes were observed from released Cu NCs at 620 nm and imidazole-2-carboxaldehyde (2-ICA) at 450 nm, respectively. With the dual-emission ratiometric strategy, efficient and rapid determination of ATP was realized, giving a detection limit down to 0.034 mM in the concentration range of 0.2 mM to 0.625 mM. The convenient synthesis process and the rapid ATP-responsive ability made the proposed Cu NCs–Al@ZIF-90 probe highly promising in clinical and environmental analysis.